Development of a Reactive Force Field for Simulations on the Catalytic Conversion of C/H/O Molecules on Cu-Metal and Cu-Oxide Surfaces and Application to Cu/CuO-Based Chemical Looping - Zhu, Wenbo; Gong, Hao; Han, You; Zhang, Minhua; van Duin, Adri C. T. (Journal of physical chemistry. C, 2020)
A fully interactive Cu/C/H/O reactive force field (ReaxFF) was developed for the Cu-metal surface catalysis system following three steps: (1) re-optimization of the Cu force field by an extended training set including additional Cu cluster properties, (2) combination of this re-optimized Cu force field and an existing C/H/O force field, and (3) fitting of interactions between Cu and C/H/O with extensive DFT data involving the various binding energies and elementary reaction steps. In addition, we developed an algorithm to search the transition state (TS) of elementary steps, which is the first TS searching program based on the ReaxFF theory framework, and a new algorithm is proposed to create reaction paths and coordinate scans with high-degrees of freedom. The comparison of results of DFT and ReaxFF indicate that the developed force field is capable of describing the properties related to reactive interactions between the Cu metal and C/H/O molecules. To test this developed Cu/C/H/O force field, a series of molecular dynamics simulations were performed. In Cu/C/H/O surface simulation, elementary C/H/O reactions involving H transfer and H₂/CHO dissociations were observed supporting the complex C/H/O interactions on a Cu surface. In addition, two Cu/CHO example cases relevant to the chemical looping combustion process were also simulated: metal oxide (CuO) generation from reactions of metallic Cu with glucose and hydrocarbon fuel oxidation using a copper oxide as the oxidizer. Our simulation results indicate that the current Cu/C/H/O ReaxFF is able to capture the reaction details and distinguish the redox performances of different fuels.